P-239 TRPV1 and TRPA1 Ion Channels in CD4+ T Cells: Novel Therapeutic Targets in IBD?. (February 2017) - Bertin, Samuel; Aoki-Nonaka, Yukari; Boland, Brigid; Chang, John; Ho, Samuel; Akopian, Armen; Franco, Alessandra; Raz, Eyal
Abstract : Background: Transient Receptor Potential Vanilloid-1 (TRPV1) and Ankyrin-1 (TRPA1) are calcium (Ca 2+ )-permeable ion channels mostly known as pain receptors in peripheral sensory neurons. However, growing evidence suggests their functional expression in other cell types, including cells of the immune system and their possible involvement in the pathogenesis of IBD. We evaluated the role TRPV1 and TRPA1 in CD4 + T cells and explored their possible contribution to T cell-mediated colitis. Methods: We used genetic and pharmacological approaches to evaluate the contribution of TRPV1 and TRPA1 to CD4 + T cell activation and function. We evaluated the effect of Trpv1 and Trpa1 gene deletion in 2 models of experimental colitis (i.e., interleukin-10 knockout and T cell adoptive transfer models). We also analyzed TRPV1 and TRPA1 gene expression and TRPV1 + TRPA1 + T cell infiltration in colonic biopsies from IBD patients. Results: We identified that TRPV1 and TRPA1 are both expressed in CD4 + T cells but play opposite functions. While TRPV1 contributes to T cell receptor (TCR)-induced Ca 2+ influx and CD4 + T cell activation, TRPA1 negatively regulates those events. Therefore, TRPV1 and TRPA1 in CD4 + T cells appear to play pro- and anti-inflammatory roles, respectively. Finally, we found differential regulation of TRPV1 and TRPA1 gene expression as well as increased infiltration of TRPV1 + TRPA1 + T cells in the colon of IBD patients. Conclusions: These studies identified TRPV1 and TRPA1 as critical regulators of T cell inflammatory responses in experimental colitis and suggest that these 2 ion channels could represent new therapeutic targets in IBD.